Analysis of Presupposition in the Story of Prophet Sulaiman and Queen Saba: A Pragmatic Study of Surah An-Naml 20-44 - Sultan Zainul Amin; Mohamad Zaka Al Farisi (al-Afkar, Journal For Islamic Studies, 2025)
This article examines presupposition in the story of Prophet Solomon and Queen Saba based on Surah An-Naml verses 20-44 with a qualitative approach and content analysis method. This research aims to identify the types of presupposition and analyze the communicative function and da'wah meaning contained in the verses. Based on George Yule's classification, six types of presupposition were found in 23 verses, namely: existential (26.09%), lexical (21.74%), active (17.39%), structural (17.39%), non-active (8.70%), and counterfactual (8.70%), Each type of presupposition plays a role in implicitly conveying da'wah messages, strengthening discourse structures, and framing ideological meanings that are unique to Qur'anic communication. This study shows that linguistic strategies in the Quran rely on explicit meaning and are full of implicit messages that can be revealed through a pragmatic approach. This finding is expected to enrich the treasures of linguistic interpretation and open up opportunities for the development of Islamic studies based on pragmatic analysis.